Análisis y rediseño del cableado estructurado de la Universidad Nacional de Loja. - Moncayo Roa, Gabriel Alexander (2017)
At present it is vital that both public and private institutions have a flexible structured cabling system that allows the integration of multiple services such as data, video, etc. And thus offer a reliable service for sending and receiving information, in a way that generates satisfaction and reliability for users. The present project, presents the analysis of the current system of structured cabling of the National University of Loja and the redesign of it with category 6a, which provides international norms and standards to improve the system in such a way as to be more efficient in its maintenance, Management of network points and support of a wide range of telecommunications products. To develop the project, a 3-phase methodology was used: In the first phase, a preliminary investigation was made on the current situation of structured cabling at the National University of Loja, once this was done, the following phases were identified The norms and standards necessary for the optimal operation of the structured cabling system and its redesign in selected areas. In addition, techniques for collecting information such as interviews and surveys were used, from which the most relevant and interesting information was extracted for the proposed purposes.